Penerapan Nilai Nilai Etika dan Pancasila Untuk Mewujudkan Kehidupan Anti Korupsi di Kalangan Generasi Z - Olipian Resky Pernando; Ilma Amelia; Naiya Aulia Putri; Nahda Ananda Putri; Anis Karlina; Ilham Hudi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to analyze the application of ethical values ​​and Pancasila in creating an anti-corruption life among generation Z. The method used is a Systematic Literature Review (SLR) which involves collecting 30 articles from Google Scholar between 2019 and 2024, which focus on the application of vethical values ​​and Pancasila in creating an anti-corruption culture, especially among generation Z. The results of this research recommend the application of these values ​​to form an anti-corruption generation Z. This research emphasizes the importance of ethical values ​​and Pancasila in the lives of students, especially generation Z in the era of globalization.